IMPLEMENTASI PEMASARAN DIGITAL DALAM MENINGKATKAN KUANTITAS SISWA BARU MELALUI KEPEMIMPINAN PARTISIPATIF DI SMKN 2 BATANGHARI - Sasmika; Jamrizal; Lukman Hakim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the implementation of digital marketing in increasing the number of new students through participatory leadership at SMKN 2 Batanghari. The research is grounded in the growing need for educational institutions to adapt to digital technology developments, particularly in school promotional strategies. This study employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The findings reveal that SMKN 2 Batanghari has utilized various digital platforms such as Instagram, Facebook, and the school’s website to enhance visibility and introduce its vocational programs to the public. Furthermore, the participatory leadership style of the principal plays a crucial role in encouraging collaboration among teachers, staff, and students in content creation and the implementation of digital marketing strategies. The synergy between digital marketing and participatory leadership positively influences the interest of prospective students. Although the increase in new student enrollment is not yet significant, the trend shows gradual improvement compared to previous years. The study concludes that digital marketing supported by participatory leadership enhances the school’s image, strengthens internal collaboration, and serves as an effective strategy to face educational competition in the digital era. Recommendations include forming a dedicated digital marketing team and improving technological literacy among school members.